(untitled) (Journal of Parents and Teachers, 2024)
Self-compassion and compassion are terms that are not always well interpreted and are sometimes out of use. However, in this digital age that inundates us, we have the great challenge of working and developing these values. Because, in education, no one gives what they do not have and because the treatment that others receive from you depends a lot on how you treat yourself. If learning is developed around human relationships, making them better, healthier and in the key of positive growth is essential.